Kemitraan Strategis Arab Saudi dengan Korea Selatan dalam Upaya Transformasi Digital Saudi Vision 2030 - Renata, Deva Dyah Renata; Eriyanti, Linda Dwi; Purwanto, Agung (Interdependence Journal of International Studies, 2026)
By using strategic partnership theory from Thomas Wilkins, this study explains how partnership between Saudi Arabia with South Korea was built for digital transformation as as part of Saudi Vision 2030. South Korea was chosen as the main partner in the implementation of Vision 2030 despite the presence of many other developed countries capable of technological development. The Saudi Arabia-South Korea partnership vision is not based on ideology or shared values ​​like most partnerships, but is developing and actively producing various two-way economic and technological cooperation agreements between the two countries. This study uses qualitative methods to explore how the partnership between the two countries is forged in digital transformation cooperation and what foundations the partnership is based on. The findings highlight that Saudi Arabia's partnership with South Korea in digital cooperation is based on the principle of peace within a multipolar cooperation system; driven by Saudi Arabia's digital transformation goals and South Korea's global market expansion; built under low commitment costs; and prioritizes beneficial economic exchanges. This write contributes to a broader understanding of how partnerships between countries are established in multipolar systems and how shared goals can bridge ideological gaps between countries in strategic partnerships.